Perilaku Kesehatan Gigi dan Mulut pada Anak Sekolah Dasar - Ida Rahmawati Julita Hendrartini Agus Priyanto (Berita Kedokteran Masyarakat (BKM), 2011)
Background: The issue of dental and oral health is a vulnerable issue faced by groups of elementary school age children. Dental Health National Data (2006) showed that the prevalence of dental caries in Indonesia was about 90% of the 238 million of Indonesian population and the number of children aged 15 years and under who sufferred from dental caries reached 76.5%. The data in 2008 from Banjar Municipal Health Office showed that the number of elementary students in Banjar District who suffered dental caries was by 65% which caused students often not to attend school.Objective: To know the factors that influence dental and oral health behaviors in elementary school children in BanjarDistrictMethods: This was an observational quantitative research using a cross sectional design. The study was conducted in Banjar District, South Kalimantan Province in two subdistricts ie Astambul and Martapura subdis-tricts. The population of this study was the mothers and elementary school age children in Banjar District. Study sample was the mothers and elementary school children in grade III aged 6-12 years old. The total sample was 126 people. The bivariate data analysis used chi-square test and logistic regression for multivariable analysis.Results: Distribution of knowledge level about dental health of elementary school children was good (54.8%); attitude of the mothers was in moderate category (45.2%); behavior of the mothers was also in moderate category (42.9%); neighborhood of elementary school children in the District Banjar was in good category (56.3%), and most of elementary school children in Banjar District had the correct behavior towards dental and oral health, with a frequency of 61.1%. The bivariate analysis showed that the variables of knowledge, attitudes, environment and behavior were significant to the children’s behavior with p-value of 0.0001, and the children’s behavior was significant with dental and oral health status with p-value of 0.0001. These results were followed with the multivariable analysis showing significance to dental health status (knowledge OR = 2.5 and p = 0.025; attitudes OR = 2.7 and p = 0.032; mother’s behavior OR = 2.9 and p = 0.027; environment OR = 3.2 and p = 0.007; children’s behavior OR = 4.6 and p = 0.018).Conclusion: The majority of mothers in Banjar District had good knowledge, attitudes, and behavior on children’s dental and oral health status. The environment of elementary school children in Banjar District was also quite positive in supporting the children’s behavior to maintain the dental and oral health status.Keywords: dental and oral health, knowledge, attitudes, behavior and environment